Reliability of tests for measuring isometric force of the muscles while shooting in basketball - Stankovic, D.; Kocic, M.; Milenkovic, S.; Bubanj, S. (Facta Universitatis: Series Physical Education and Sport, 2020)
The aim of this research is to determine the isometric muscle force (IMF) of the dominant arm in the position directly before the basketball shooting, and to check test reliability. Fifteen male basketball players (age 17±1 years, body height 185.60±6.31 cm; body mass 78.07±8.56 kg) with at least 5 years of the basketball experience, were subjected to a muscle manual test (shoulder flexion, elbow extension and wrist flexion), using a hand-held dynamometry (HDD). High values of relative reliability are reported in each of the tests (0.79, 0.82, and 0.84, respectively). Cronbach's alpha coefficient indicated the values of reliability during shoulder flexion, elbow extension and wrist flexion range from 0.779, 0.807, 0.848 respectively, presenting the results of the reliability as high. The applied F test provides a statistically significant Intraclass Correlation Coefficient at the level of p<0.001 for each test. Absolute reliability is displayed through the coefficient of variation, and meets the criterion which ranged between 5.6 to 7.8%. HDD was determined to be reliable in terms of measuring IMF.